Does Trust Promote Growth? - Roman Horváth (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
We examine the effect of generalized trust on long-term economic growth. Unlike in previous studies, we use Bayesian model averaging to deal rigorously with model uncertainty and attendant omitted variable bias. In addition, we address endogeneity and assess whether the effect of trust on growth is causal. Examining more than forty regressors for nearly fifty countries, we show that trust exerts a positive effect on long-term growth and, based on the posterior inclusion probabilities, suggest that trust is an important driver of long-term growth. Our results also show that trust is key for growth in countries with a weak rule of law.
urn:nbn:de:101:1-201207106486
Keywords: O43; O10; Z13; 330; trust; economic growth; Bayesian model averaging; Vertrauen; Wirtschaftswachstum; Schätzung; Welt